2019
DOI: 10.3390/microorganisms7120657
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Phenyl Acid Dynamics during the Start-up Phase of Anaerobic Straw Degradation in Meso- and Thermophilic Batch Reactors

Abstract: Aromatic compounds like phenyl acids derived from lignocellulose degradation have been suspected to negatively influence biogas production processes. However, results on this topic are still inconclusive. To study phenyl acid formation in batch reactors during the start-up phase of anaerobic degradation, different amounts of straw from grain were mixed with mesophilic and thermophilic sludge, respectively. Molecular biological parameters were assessed using next-generation sequencing and qPCR analyses. Metagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…Furthermore, 288 genomes and 359 KEGG pathways were observed for this data set, including all mesophilic as well as all thermophilic normalised samples. These numbers are comparable to a previous study focusing on the two meso-and thermophilic methanogenic systems [40]. Generally, the orthology counts for peripheral and central benzoyl-CoA pathways were considerably higher in mesophilic than in thermophilic samples (Fig.…”
Section: Prediction Of Metagenomic Properties (Piphillin)supporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, 288 genomes and 359 KEGG pathways were observed for this data set, including all mesophilic as well as all thermophilic normalised samples. These numbers are comparable to a previous study focusing on the two meso-and thermophilic methanogenic systems [40]. Generally, the orthology counts for peripheral and central benzoyl-CoA pathways were considerably higher in mesophilic than in thermophilic samples (Fig.…”
Section: Prediction Of Metagenomic Properties (Piphillin)supporting
confidence: 88%
“…The small subunit rRNA gene primers 515f and 806r [69], according the Earth microbiome project [70], were used to target the V4 region. The first PCR step, including the 16S rRNA primers and the Illumina ® adapter sequences, was performed as described previously [40]. 25 µL PCR solution contained 12 µL PCR Mix (MyTaq ™ Mix 2× (Bioline), 250 nM of each primer-adapter combination, 20% Betaine Enhancer Solution (5×) (VWR International, Germany), and PCR-grade water to reach a final volume of 24 µL, as well as 1 µL DNA template (2.5 ng DNA µL −1 ).…”
Section: Ngs Library and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…One group of monocyclic aromatic compounds are phenyl acids that include phenylacetate (PAA), phenylpropionate (PPA), or phenylbutyrate (PBA). Studies on PPA [ 18 ] and especially on PBA [ 19 ] are very rare, even though they represent relevant intermediates in the AD cascade prior to the anaerobic ring cleavage. A cascade-like increase/decrease from PAA to PPA to PBA could be observed when straw from grain was anaerobically degraded under overload conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A cascade-like increase/decrease from PAA to PPA to PBA could be observed when straw from grain was anaerobically degraded under overload conditions. It was concluded that an increase in PAA concentration was an early indicator for overload conditions, whereas an increase in PBA concentration indicated a switch from using easier degradable substrates to more recalcitrant (lignocellulosic) materials [ 19 ].…”
Section: Introductionmentioning
confidence: 99%